Combination of Hypofractionated Radiation Therapy and Gilvetmab for the Treatment of Cutaneous or Subcutaneous Mast Cell Tumours in Dogs - Tiffany W. Martin; Douglas H. Thamm; Kristen M. Weishaar (Veterinary and Comparative Oncology, 2026)
ABSTRACT Gilvetmab is a caninised monoclonal antibody against canine PD‐1. Concurrent or sequential administration of anti‐PD‐1 antibodies and radiation therapy (RT) improves survival time in various species. Eighteen dogs with mast cell tumours (MCTs) were prospectively treated with 24 Gy of RT over Days 0, 7 and 21 and gilvetmab every 2 weeks beginning on the second fraction of RT (Day 7) for up to 10 doses. Best tumour response was complete in one (6%), partial in eight (44%) and stable disease in nine dogs (50%) for an ORR of 50%. Median time to best response was 7 days after the first fraction of RT. Thirteen dogs (72%) developed progressive disease with a median progression free interval (PFI) of 116 days after the first fraction of RT. Nine adverse events (AEs) attributed to gilvetmab were recorded in seven dogs (39%) consisting of infusion reactions in four, metabolic changes in three and gastrointestinal signs and pancreatitis in one each. Overall, five dogs (28%) experienced Grade 3 AEs. Radiation AEs were limited to Grade 1 for both acute and late effects in seven dogs (39%). There was a significant difference in PFI and MST for dogs with and without lymph node metastasis with a median PFI of 64 versus 292 days and MST of 103 versus 587 days ( p = 0.02 and 0.005, respectively). This sequence, or combination, of therapies did not provide durable tumour control for canine MCT and the AE profile warrants further evaluation.